1‐Bit reconfigurable transmitarray with low insertion loss for wireless power transmission. Issue 11 (14th August 2022) - Shuai, Kang; Liu, Changrong; Yang, Xinmi; Liu, Xueguan
Abstract: A 1‐bit reconfigurable transmitarray (RTA) is studied in this article for wireless power transmission (WPT). The type of the RTA is micro‐element embedded active frequency selective surface (AFSS). First, parameters of the 1‐bit RTA unit‐cell are obtained at 5.8 GHz through equivalent circuit analysis and HFSS simulation. After optimization, the maximum insertion loss of the unit‐cell at 5.8 GHz is 0.96 dB, a 180‐degree phase difference can be got when pin diodes reverse and forward biased, and the size of the unit‐cell is about 0.42 λ 0 . Second, composing the unit‐cell to 11 × 11 AFSS, the beam‐steering of ±40° in XOZ ‐plane and YOZ ‐plane can be achieved, while feeding layer effect is to be discussed. Finally, the beam‐steering performance of this AFSS is verified through testing. The dimensions of each FSS board are 260.9 × 260.9 × 0.8 mm 3 and 0/1 distribution is controlled by field‐programmable gate array (FPGA). The measured results are basically consistent with the simulation ones in beam steering. The difference of the peak gain in the main direction is analyzed.